Impoliteness Strategies Used by the Employees of Karen’s Diner in Serving Their Customers - Cindy Cornelia; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This research paper focuses on the impoliteness strategies employed by the employees of Karen's Diner in serving their customers. Through this research, I would like to know how Karen's Diner’s employees apply impoliteness as a strategy in communicating with their customers and why they use the impoliteness strategies. To support this research, I use the theory of impoliteness by Jonathan Culpeper (1996, 2005, 2011). In this study, I discovered that Karen's Diner employees apply impoliteness as several strategies, including by rejecting customers, by ordering customers, by warning customers, and by insulting customers. In addition, I also discovered that the employees of Karen's diner use the four impoliteness strategies to entertain their customers that can be seen from the positive reactions given by customers to the impoliteness treatments from the employees such as saying that they enjoy being at Karen's Diner, they recommend other people to visit Karen's Diner, and they will return to Karen's DIner.